Patient Phenotypes Help Explain Variation in Response to a Social Gamification Weight Loss Intervention. Issue 3 (March 2020) - Lienert, Jeffrey; Patel, Mitesh
Purpose: This study aims to determine latent classes of study participants using baseline characteristics, explore the patterns within the groups, and determine whether the intervention had differential effects on weight loss across the groups. Design: Secondary analysis of a completed randomized clinical trial. Setting: Participants in a gamification intervention with social incentives who were recruited as pairs and given an intervention for 24 weeks. Participants were randomized to control, gamification, or gamification with primary care physician sharing arms. Participants: All 196 participants in the Lose It trial (recruited as 98 pairs). Measures: Outcome variable—participants' weight change after 24 and 36 weeks. Factors—intervention arm and latent class. Analysis: Latent class analysis on both participants' and teams' characteristics. This was followed by 1-sample t tests of weight at 24 and 36 weeks, stratified by latent class. Results: Three groups of participants were identified: "Kin teams, " "Distant teams, " and "Married teams." "Kin teams" lost more weight after the intervention in the gamification and gamification with PCP sharing arms. The "Distant teams" lost similar amounts of weight in all 3 arms but did not keep it off during maintenance. The "Married teams" lost the most weight across all 3 arms and kept it off following the intervention. Conclusions: Patient phenotypes can identify variations in response to a gamification weight loss intervention. Future intervention studies may benefit from leveraging this during participant recruitment and allocation.